2021
DOI: 10.3389/fimmu.2021.777606
|View full text |Cite
|
Sign up to set email alerts
|

Role of Toll-Like Receptors in Neuroimmune Diseases: Therapeutic Targets and Problems

Abstract: Toll-like receptors (TLRs) are a class of proteins playing a key role in innate and adaptive immune responses. TLRs are involved in the development and progression of neuroimmune diseases via initiating inflammatory responses. Thus, targeting TLRs signaling pathway may be considered as a potential therapy for neuroimmune diseases. However, the role of TLRs is elusive and complex in neuroimmune diseases. In addition to the inadequate immune response of TLRs inhibitors in the experiments, the recent studies also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 218 publications
0
13
0
Order By: Relevance
“…As current treatments for HIV NCIs only attenuate the symptoms, elucidating any potential mechanism(s) of TLR-mediated neuroinflammation in the CNS of PLWH may be important for the development of therapeutics to prevent NCI not only in HAND, but also in other neurodegenerative diseases. Indeed, the targeting of TLRs and their downstream signalling pathways as a potential therapeutic approach has already demonstrated efficacy in animal models of several neurodegenerative diseases, including Alzheimer's disease and Parkinson's disease, by suppressing microglia activation and neuroinflammation [83][84][85]. As IRAK1 is a key component of both IL-1R and TLR-mediated signalling, the pharmacological inhibition of IRAK1 thus has potential Each symbol represents the mean of an individual biological replicate performed in triplicate; small horizontal lines indicate the grand means of four biological replicates±sd.…”
Section: Discussionmentioning
confidence: 99%
“…As current treatments for HIV NCIs only attenuate the symptoms, elucidating any potential mechanism(s) of TLR-mediated neuroinflammation in the CNS of PLWH may be important for the development of therapeutics to prevent NCI not only in HAND, but also in other neurodegenerative diseases. Indeed, the targeting of TLRs and their downstream signalling pathways as a potential therapeutic approach has already demonstrated efficacy in animal models of several neurodegenerative diseases, including Alzheimer's disease and Parkinson's disease, by suppressing microglia activation and neuroinflammation [83][84][85]. As IRAK1 is a key component of both IL-1R and TLR-mediated signalling, the pharmacological inhibition of IRAK1 thus has potential Each symbol represents the mean of an individual biological replicate performed in triplicate; small horizontal lines indicate the grand means of four biological replicates±sd.…”
Section: Discussionmentioning
confidence: 99%
“…GWAS also uncovered that up to 10.5% of the genetic variance underlying MS risk is linked to human leukocyte antigen (HLA) class II alleles among all ethnic groups studied [29]. However, studies have also revealed that non-HLA loci and their SNPs may influence susceptibility to MS, especially those involved in controlling components involved in innate and adaptive immune responses; for instance, cytokines and TLRs [12,16,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated expression of TLRs has been shown to correlate with immune imbalances, suggesting an increased risk of inflammatory and autoimmune diseases, and similar evidence has been indicated in neuroimmune diseases. Besides, the potential of TLRs as therapeutic targets in these diseases has been suggested [11,12]. In MS, studies have indicated that TLRs play a critical role in pathogenesis of disease; for instance, TLR3 and TLR4 expression was shown to be significantly upregulated in MS lesions, and both TLRs were positively correlated with MS pathogenesis, particularly in patients with RRMS [13].…”
Section: Introductionmentioning
confidence: 99%
“…OxS was found to be associated with mitochondrial dysfunction, dysregulation of axonal bioenergetics and iron accumulation in the brain ( Adamczyk and Adamczyk-Sowa, 2016 ). Recent research has shown that TLRs play a crucial role in the pathogenesis and progression of neuroimmune diseases by triggering an inflammatory response ( Li et al, 2021 ). The expression of TLR3 and TLR4 was significantly increased in the center of MS lesions and around inflamed vessels in human postmortem brain tissues ( Bsibsi et al, 2002 ).…”
Section: Non-communicable Diseases Caused By Smoking: Dysregulation O...mentioning
confidence: 99%